Simultaneous modified Camitz opponensplasty using a pulley at the radial side of the flexor retinaculum in severe carpal tunnel syndrome. (July 2014) - Kato, N.; Yoshizawa, T.; Sakai, H.
Camitz opponensplasty using the palmaris longus has been used in patients undergoing open carpal tunnel release. It is considered to have several advantages over other opponensplasty techniques, but it provides weak flexion and pronation, which are prerequisites for opposition. To address this shortcoming, we have used a modified Camitz procedure with a pulley at the radial side of the dissected flexor retinaculum and have assessed the results in comparison with the conventional Camitz procedure. Both procedures provided significant improvements in palmar abduction and Disabilities of the Arm, Shoulder, and Hand and Kapandji scores at 3 months post-operatively, but patients who underwent the modified Camitz procedure showed better improvement in pulp pinch, palmar abduction, and thumb pronation.